2020
DOI: 10.1093/database/baaa106
|View full text |Cite
|
Sign up to set email alerts
|

RegulomePA: a database of transcriptional regulatory interactions in Pseudomonas aeruginosa PAO1

Abstract: We present RegulomePA, a database that contains biological information on regulatory interactions between transcription factors (TFs), sigma factor (SFs) and target genes in Pseudomonas aeruginosa PAO1. RegulomePA consists of 4827 regulatory interactions between 2831 nodes, which represent the interactions of TFs and SFs with their target genes, from the total of predicted RegulomePA including 27.27% of the TFs, 54.16% of SFs and 50.8% of the total genes. Each entry in the database corresponds to one node in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 22 publications
(15 reference statements)
0
23
0
Order By: Relevance
“…There is no straightforward nor standard way to infer a global regulatory network. A few precomputed inferences based on sequence or transcriptomics are scattered across the literature and organism-specific databases ( Galan-Vasquez et al, 2020 ; Parise et al, 2020 ). Most of these inferences come from different approaches making it difficult to assess them.…”
Section: Dealing With Grns Incompletenessmentioning
confidence: 99%
“…There is no straightforward nor standard way to infer a global regulatory network. A few precomputed inferences based on sequence or transcriptomics are scattered across the literature and organism-specific databases ( Galan-Vasquez et al, 2020 ; Parise et al, 2020 ). Most of these inferences come from different approaches making it difficult to assess them.…”
Section: Dealing With Grns Incompletenessmentioning
confidence: 99%
“…(38,39) Studies have shown a scale-free structure in cellular metabolic networks, (32,40) protein interaction networks, including in câncer, (41,42) transcription regulatory networks, and GRN. (20,(43)(44)(45) Following the literature, (36,37,(46)(47)(48) there is some qualitative and quantitative characteristics to ensure that a network is scale-free: the power-law distribution appears as a straight line on a logarithmic plot; the γ value usually is in the range 2<γ<3; and the presence of high-degree nodes, called hubs, dominating the network, with most nodes clustered around them.…”
Section: Methodsmentioning
confidence: 99%
“…(65) Scales, dplyr, tibble, readr and igraph packages were used for data manipulation and plotting of the structural analyses. (2,20,66) The igraph library was used to compute most of the properties described above: the in and out degrees, centrality, clustering coefficients, feed-forward loop motifs, connectivity, cycles, paths, and hierarchical levels analyses. (67) The illustrations of the GRN, the hub's network and the connectivity analysis were made in Cytoscape.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations